Pengaruh Kesadaran Pajak, Sanksi Perpajakan, dan Digitalisasi Perpajakan terhadap Kepatuhan Wajib Pajak Orang Pribadu UMKM dengan Kualitas Pelayanan sebagai Variabel Moderasi: Studi pada Wajib Pajak Orang Pribadi UMKM yang Terdaftar pada KPP Wilayah Jakar - Vidia Juliyanti; Wedi Rusmawan Kusumah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effects of taxpayer awareness, tax sanctions, and tax digitalization on the tax compliance of individual Micro, Small, and Medium Enterprise (MSME) taxpayers, with service quality as a moderating variable. The study was conducted on individual MSME taxpayers registered at the Tax Service Offices (KPP) in South Jakarta and South Tangerang. A quantitative research approach with a survey method was employed. Primary data were collected through questionnaires distributed to 260 respondents selected using purposive sampling. Data were analyzed using IBM SPSS Statistics through validity and reliability tests, classical assumption tests, multiple linear regression analysis, and Moderated Regression Analysis (MRA). The findings indicate that taxpayer awareness, tax sanctions, and tax digitalization each have a positive and significant effect on MSME taxpayer compliance. These results suggest that improving taxpayers' awareness, implementing consistent tax sanctions, and optimizing digital tax services contribute to higher levels of tax compliance. However, service quality was not found to moderate the relationship between taxpayer awareness, tax sanctions, or tax digitalization and taxpayer compliance. This finding indicates that service quality plays a more direct role in improving taxpayer compliance rather than strengthening the influence of the independent variables. The results of this study are expected to provide practical implications for the Directorate General of Taxes in formulating policies aimed at improving taxpayer awareness, strengthening tax law enforcement, accelerating tax digital transformation, and enhancing service quality to increase tax compliance among MSMEs.